Incidence, Admission Rates, and Economic Burden of Adult Emergency Visits for Chronic Pancreatitis: Data From the National Emergency Department Sample, 2006 to 2012. Issue 8 (September 2019) - Garg, Sushil K.; Singh, Dupinder; Sarvepalli, Shashank; Bazerbachi, Fateh; Puthanveedu, Nitin D.; Obaitan, Itegbemie; Haffar, Samir; Goyal, Hemant; Sanaka, Madhusudhan R.
Abstract : Introduction: Chronic pancreatitis (CP) is a common reason for emergency department (ED) visits, but little research has examined ED use by patients with CP. Materials and Methods: The Nationwide Emergency Department Sample (2006 to 2012) was interrogated to evaluate trends in adult ED visits for a primary diagnosis of CP (International Classification of Disease, 9th revision, Clinical Modification code: 577.1), the rates of subsequent hospital admission, and total charges. A survey logistic regression model was used to determine factors associated with hospitalization from the ED. Results: We identified 253, 753 ED visits with a primary diagnosis of CP. No significant trends in annual incidence were noted. However, the ED-to-hospitalization rates decreased by 3% per year ( P <0.001) and mean ED charges after adjusting for inflation increased by 11.8% per year ( P <0.001). Higher Charlson comorbidity index, current smoker status, alcohol use, and biliary-related CP were associated with hospitalization. In hospitalized patients, length of stay decreased by 2.2% per year ( P =0.003) and inpatient charges increased by 2.9% per year ( P =0.004). Conclusions: Patient characteristics associated with higher risk of hospitalization from the ED deserve further attention.